3D Biometrics for Hindfoot Alignment Using Weightbearing CT. (June 2017) - Lintz, François; Welck, Matthew; Bernasconi, Alessio; Thornton, James; Cullen, Nicholas P.; Singh, Dishan; Goldberg, Andy
Background: Hindfoot alignment on 2D radiographs can present anatomical and operator-related bias. In this study, software designed for weightbearing computed tomography (WBCT) was used to calculate a new 3D biometric tool: the Foot and Ankle Offset (FAO). We described the distribution of FAO in a series of data sets from clinically normal, varus, and valgus cases, hypothesizing that FAO values would be significantly different in the 3 groups. Methods: In this retrospective cohort study, 135 data sets (57 normal, 38 varus, 40 valgus) from WBCT (PedCAT; CurveBeam LLC, Warrington, PA) were obtained from a specialized foot and ankle unit. 3D coordinates of specific anatomical landmarks (weightbearing points of the calcaneus, of the first and fifth metatarsal heads and the highest and centermost point on the talar dome) were collected. These data were processed with the TALAS system (CurveBeam), which resulted in an FAO value for each case. Intraobserver and interobserver reliability were also assessed. Results: In normal cases, the mean value for FAO was 2.3% ± 2.9%, whereas in varus and valgus cases, the mean was −11.6% ± 6.9% and 11.4% ± 5.7%, respectively, with a statistically significant difference among groups ( P < .001). The distribution of the normal population was Gaussian. The inter- and intraobserver reliability were 0.99 +/- 0.00 and 0.97 +/-0.02 Conclusions: This pilot study suggests that the FAO is an efficient tool for measuring hindfoot alignment using WBCT. Previously published research in this field has looked at WBCT by adapting 2D biometrics. The present study introduces the concept of 3D biometrics and describes an efficient, semiautomatic tool for measuring hindfoot alignment. Level of Evidence: Level III, retrospective comparative study.